Dairy Products plant - Rivera, Maria Mercedes A.; Rubio, Herminia R.; Valenzuela, Sonia G. (Diliman, Quezon City College of Engineering, 1963)
Herewith is a plant design on the production of 139,800 pints pasteurized milk, 793,500 pounds powdered skim milk, 707,700 pounds cheese, 739,800 pounds butter annually with P2,797,00 fixed capital, P3,644,300 annual manufacturing plant cost and P3,295,350 annual total cost. The annual production sales amount to P4,161,530. Break-even point is at 34 percent.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Dairy plants; Milk plants